Elementary mathematics teachers' judgment accuracy and calibration accuracy: Do they predict students' mathematics achievement outcomes?. (October 2016) - Gabriele, Anthony J.; Joram, Elana; Park, Ki H.
Abstract: In this study we investigated whether elementary mathematics teachers' knowledge of their students, as reflected in both the accuracy and confidence with which they are able to estimate their students' task-specific performance on sets of mathematics problems, predicted students' overall mathematics achievement. Thirty-nine teachers made predictions about the performance of a random sample of target students ( n  = 150) in their classrooms on sets of "easy" and "difficult" multiplication and division problems. Teachers also provided confidence ratings for those judgments. From these data, indicators of teachers' judgment accuracy, judgment confidence and calibration accuracy (a measure of metacognitive monitoring) were then related to all of their students' ( n  = 834) performance on year-end standardized mathematics achievement tests. Multilevel analyses indicate that teachers' calibration accuracy, but not their task-specific judgment accuracy, significantly predicted students' mathematics achievement. Implications for future research on teacher knowledge as well as professional development programs are discussed. Highlights: Teachers differ in the accuracy of their judgments about their students. Teachers differ in the degree of over/underconfidence in judgments about students. Judgment accuracy does not predict student achievement in mathematics. Over/underconfidence (i.e., calibration accuracy) predicts student achievement. Calibration accuracy may be a useful tool for teachers' professional development.